A pilot investigation of acute inhibitory control training in cocaine users. (1st May 2017) - Alcorn, Joseph L.; Pike, Erika; Stoops, William S.; Lile, Joshua A.; Rush, Craig R.
Highlights: Acute inhibitory control training tested in cocaine users. Cocaine users were assigned to cocaine or neutral cue training. Improved response inhibition performance was observed in both conditions. Cocaine-cue attentional bias was not altered by acute inhibitory control training. Abstract: Background: Disrupted response inhibition and presence of drug-cue attentional bias in cocaine-using individuals have predicted poor treatment outcomes. Inhibitory control training could help improve treatment outcomes by strengthening cognitive control. This pilot study assessed the effects of acute inhibitory control training to drug- and non-drug-related cues on response inhibition performance and cocaine-cue attentional bias in cocaine-using individuals. Methods: Participants who met criteria for a cocaine-use disorder underwent five sessions of inhibitory control training to either non-drug-related cues (i.e., rectangles) or cocaine cues (n = 10/condition) in a single day. Response inhibition and attentional bias were assessed prior to and following training using the stop-signal task and visual-probe task with eye tracking, respectively. Results: Training condition groups did not differ on demographics, inhibitory control training performance, response inhibition, or cocaine-cue attentional bias. Response inhibition performance improved as a function of inhibitory control training in both conditions. Cocaine-cue attentional bias was observed, but did not change as a function of inhibitory control training in either condition. Conclusions: Response inhibition in cocaine-using individuals was augmented by acute inhibitory control training, which may improve treatment outcomes through better behavioral inhibition. Future studies should investigate longer-term implementation of inhibitory control training, as well as combining inhibitory control training with other treatment modalities.